Hydrochlorothiazide Potentiates Contractile Activity of Mouse Cavernosal Smooth Muscle. Issue 2 (19th March 2016) - Gagliano-Jucá, Thiago; Napolitano, Mauro; Del Grossi Ferraz Carvalho, Fernanda; Campos, Rafael; Mónica, Fabíola Zakia; Claudino, Mário Angelo; Antunes, Edson; Lopes, Anibal Gil; De Nucci, Gilberto
Abstract: Introduction: Hydrochlorothiazide has a negative influence on penile erection but little is known about the mechanism(s) involved. Aims: To characterize the effects of this diuretic on mouse corpus cavernosum (CC) smooth muscle in vitro and ex vivo. Methods: CC strips of C57BL/6 mice (12–16 weeks old) were mounted in organ baths containing Krebs-Henseleit solution and tissue reactivity was evaluated. Expression of genes encoding diuretic targets and enzymes involved in penile erection were evaluated by polymerase chain reaction. Main Outcome Measures: Stimulation-response curves to phenylephrine (10 nmol/L–100 μmol/L) or to electrical field stimulation (1–32 Hz) were constructed, with or without hydrochlorothiazide. Strips of CC from mice after long-term hydrochlorothiazide treatment (6 mg/kg/day for 4 weeks) with or without amiloride (0.6 mg/kg/day for 4 weeks) in vivo also were studied. Nitric oxide and Rho-kinase pathways were evaluated. Results: Hydrochlorothiazide (100 μmol/L) increased the maximum response to phenylephrine by 64% in vitro. This effect was unaffected by the addition of indomethacin (5 μmol/L) but was abolished by N( ω )-nitro-L-arginine methyl ester (100 μmol/L). Hydrochlorothiazide (100 μmol/L) potentiated electrical field stimulation-induced contraction in vitro, but not ex vivo. Long-term treatment with hydrochlorothiazide increased the maximum response to phenylephrine by 60% and resulted in a plasma concentration of 500 ± 180 nmol/L. Amiloride (100μmol/L) caused rightward shifts in concentration-response curves to phenylephrine in vitro. Long-term treatment with hydrochlorothiazide plus amiloride did not significantly increase the maximum response to phenylephrine (+13%). Reverse transcriptase polymerase chain reaction did not detect the NaCl cotransporter in mouse CC. Hydrochlorothiazide did not change Rho-kinase activity, whereas amiloride decreased it in vitro and ex vivo (approximately 18% and 24% respectively). A 40% decrease in Rock1 expression also was observed after long-term treatment with hydrochlorothiazide plus amiloride. Conclusion: Hydrochlorothiazide potentiates contraction of smooth muscle from mouse CC. These findings could explain why diuretics such as hydrochlorothiazide are associated with erectile dysfunction.